2017
DOI: 10.1136/gutjnl-2017-314548
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A11 is targeted by IgG4 and IgG1 autoantibodies in IgG4-related disease

Abstract: Our data suggest that IgG1-mediated pro-inflammatory autoreactivity against annexin A11 in patients with IgG4-RD may be attenuated by formation of annexin A11-specific IgG4 antibodies supporting an anti-inflammatory role of IgG4 in IgG4-RD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
123
1
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(135 citation statements)
references
References 36 publications
5
123
1
6
Order By: Relevance
“…With antibody response frequencies of only 7%, 10%, 12%, and 28% for laminin 511‐E8, prohibitin, annexin A11, and galectin‐3, respectively, it seems clear that none of these autoantigens constitutes a dominant antigen in the context of IgG4‐RD. Additionally, we did not observe any organ‐specific enrichment for pancreatic or biliary involvement among the patients with autoantibodies directed against annexin A11 and laminin 511‐E8 . The frequencies of antibody responses against these 2 autoantigens among subsets of our patients with AIP or AIC were comparable to those previously reported: 22% versus 18% for annexin A11 in AIP/AIC patients , and 12.5% versus 10% for laminin 511‐E8 in AIP patients .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…With antibody response frequencies of only 7%, 10%, 12%, and 28% for laminin 511‐E8, prohibitin, annexin A11, and galectin‐3, respectively, it seems clear that none of these autoantigens constitutes a dominant antigen in the context of IgG4‐RD. Additionally, we did not observe any organ‐specific enrichment for pancreatic or biliary involvement among the patients with autoantibodies directed against annexin A11 and laminin 511‐E8 . The frequencies of antibody responses against these 2 autoantigens among subsets of our patients with AIP or AIC were comparable to those previously reported: 22% versus 18% for annexin A11 in AIP/AIC patients , and 12.5% versus 10% for laminin 511‐E8 in AIP patients .…”
Section: Discussionsupporting
confidence: 84%
“…Since 2015, 4 autoantigens have been described as potential triggers for IgG4‐RD: prohibitin, annexin A11, laminin 511‐E8, and galectin‐3 . However, validation of these findings using external patient cohorts and characterization of the relationship between these specific autoantigens has yet to be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Current evidence suggests that IgG4-RD is an immune-mediated process but target autoantigen(s) and the effector cells have not been fully identified. Recently, annexin A11, an intracellular protein, has been identified as a novel autoantigen in AIP and IgG4-SC 10. A potential role of exposure to occupational antigens has been suggested by cohort studies that observed a higher prevalence of the disease among ‘blue-collar workers’ (eg, building contractors, plumbers).…”
Section: Overview Of Igg4-rdmentioning
confidence: 99%
“…1 IgG4-related sclerosing cholangitis and autoimmune pancreatitis are the biliary and pancreatic manifestations of this disease. A role for IgG4 (auto) antibodies in disease pathogenesis is supported by three observations: (i) oligoclonal expansion of IgG4 + -dominant B-cell receptor (BCR) clones in the blood and tissue of patients with active IgG4-RD 2 ; (ii) the identification of IgG4 autoantibodies (annexin A11-specific) in a proportion of IgG4-RD patients 3 ; and (iii) B-cell depletion therapy with rituximab, which attenuates disease activity and selectively depletes the IgG4 subclass. 4 Furthermore, a recent study demonstrated pancreatic injury in BALB/c mice induced by injection of IgG4 antibodies purified from patients with autoimmune pancreatitis, although more destructive changes were exhibited by injection of IgG1 antibodies, and IgG4 inhibited the pathogenic effects of IgG1 on simultaneous injection.…”
Section: Introductionmentioning
confidence: 99%